A fast and accurate method for the seismic response analysis of reinforced concrete frame structures considering Beam-Column joint deformation. (15th January 2022) - Yu, Ding-Hao; Li, Gang; Dong, Zhi-Qian; Li, Hong-Nan
Highlights: A inelasticity-separated RC frame model considering beam-column joint is presented. The structural stiffness matrix can keep unchanged by adding some inelastic DOFs. The proposed elements for bond slip and joint shear produce high accurate results. The use of Woodbury formula improve computational efficiency greatly. Abstract: Many previous investigations of reinforced concrete (RC) frame structures have demonstrated that beam-column joints may experience significant nonlinearities under earthquake excitations. However, most available analysis methods assume that the joint region remains rigid. Because joint failure may result in strength and stiffness losses and even induce structural collapse, it is difficult for an analytical model with a rigid joint assumption to obtain an accurate prediction of the structural nonlinear response. The behavior of a joint is mainly affected by the shear deformation of the joint core and bond-slip of beam longitudinal reinforcements in the joint. Although many different types of modeling approaches have been presented to effectively represent the behavior mechanism of beam-column joints, the introduction of joint models inevitably increases the complexity of the analytical model of the global structure and the effort of the solution process. Therefore, achieving highly efficient analysis on the premise of accurately predicting the seismic response of RC frame structures is still a topic that deserves investigation. This study presents an efficient analysis method for the accurate evaluation of the nonlinear response of RC frames considering the effect of beam-column joint deformation based on the concept of local inelasticity separation. The proposed method captures the bond-slip behavior at beam ends by adding inelastic rotation hinge mechanisms to the ends of the existing inelasticity-separated fiber beam-column model and uses a sliding hinge mechanism to simulate the inelastic shear response of the joint core. A small number of additional inelastic degrees of freedom that are separated from the global displacement degrees of freedom of the structure is introduced to describe both the inelastic rotation behavior and the inelastic deformation of the proposed bond-slip hinge mechanism and the sliding hinge mechanism. Consequently, the Woodbury formula can be utilized for nonlinear iterative solutions to avoid updating the global stiffness matrix, thus significantly improving the computational efficiency. The exactness of the proposed method is verified against experimental data, and its application is illustrated through a seismic response analysis example.